2013
DOI: 10.1002/cctc.201200591
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Catalysis over Bimetallic Alloy Nanoparticles

Abstract: Bimetallic nanoparticles (NPs) have emerged as an important class of catalysts. In many cases, bimetallic alloy NPs have higher catalytic efficiencies than their monometallic counterparts, owing to strong synergy between the metals. In this Review, we survey the research progress on the synergistic effect of bimetallic alloy NPs for catalytic reactions related to fuel cells, such as the electrochemical oxidation of MeOH, EtOH, and formic acid, CO oxidation, the oxygen‐reduction reaction, and the dehydrogenatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
432
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 610 publications
(439 citation statements)
references
References 221 publications
4
432
0
3
Order By: Relevance
“…The enhancement in electrocatalytic activity has been attributed to the synergistic effect of the surface electronic states on the effective atomic coordination number. 14 In particular, it has been found that Pt in Au-Pt alloy nanoparticles plays an important role in enhancing catalytic activity.…”
Section: Optimization Of Au/pt Synthetic Ratio For Hydroxylamine Detementioning
confidence: 99%
See 1 more Smart Citation
“…The enhancement in electrocatalytic activity has been attributed to the synergistic effect of the surface electronic states on the effective atomic coordination number. 14 In particular, it has been found that Pt in Au-Pt alloy nanoparticles plays an important role in enhancing catalytic activity.…”
Section: Optimization Of Au/pt Synthetic Ratio For Hydroxylamine Detementioning
confidence: 99%
“…The improvements derived from the combination of two metal elements into bimetallic nanoparticles can be attributed to synergistic effects. 14 In particular, Au-Pt alloy nanoparticles have been extensively researched because the Au-Pt bimetallic system has greater catalytic activity and enhanced functionalities than pure Pt or Au. 15 However, it is challenging to synthesize single-phase Au-Pt alloys because they are immiscible in the bulk.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, green synthesis of nanoparticles using biomaterials is attractive to most scientists due to its simplicity and eco-friendliness. Bimetallic nanostructures are also more attractive for a wide range of catalytic and electrocatalytic applications over their monometallic counterparts due to combined properties of the two individual metals and the synergy that exists between the two metals [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The application of bimetallic NPs including alloys and core-shell structures are gaining interest due to their enhanced activity or selectivity. 1,2 Continuing developments in colloidal synthesis is enabling greater control of structural and chemical features at the nanoscale. The majority of catalytic applications requires immobilisation of colloidal NPs onto support materials, with activated carbon or nonporous oxide supports most commonly used for pre-synthesized NPs, however incorporation of NPs into porous supports is desirable.…”
Section: Introductionmentioning
confidence: 99%